Cytological observation and transcriptome analysis reveal dynamic changes of Rhizoctonia solani colonization on leaf sheath and different genes recruited between the resistant and susceptible genotypes in rice - Liu, Sanglin; Wang, Tianya; Meng, Guoxian; Liu, Jiahao; Lu, Dibai; Liu, Xiangdong; Zeng, Yuxiang (Frontiers in Plant Science, 2022)
Sheath blight, caused by Rhizoctonia solani, is a big threat to the global rice production. To characterize the early development of R. solani on rice leaf and leaf sheath, two genotypes, GD66 (a resistant genotype) and Lemont (a susceptible genotype), were observed using four cytological techniques: the whole-mount eosin B-staining confocal laser scanning microscopy (WE-CLSM), stereoscopy, fluorescence microscopy, and plastic semi-thin sectioning after in vitro inoculation. WE-CLSM observation showed that, at 12 h post-inoculation (hpi), the amount of hyphae increased dramatically on leaf and sheath surface, the infection cushions occurred and maintained at a huge number from about 18 to 36 hpi, and then the infection cushions disappeared gradually from about 42 to 72 hpi. Interestingly, R. solani could not only colonize on the abaxial surfaces of leaf sheath but also invade the paraxial side of the leaf sheath, which shows a different behavior from that of leaf. RNA sequencing detected 6,234 differentially expressed genes (DEGs) for Lemont and 7,784 DEGs for GD66 at 24 hpi, and 2,523 DEGs for Lemont and 2,719 DEGs for GD66 at 48 hpi, suggesting that GD66 is recruiting more genes in fighting against the pathogen. Among DEGs, resistant genes, such as OsRLCK5, Xa21, and Pid2, displayed higher expression in the resistant genotype than the susceptible genotype at both 24 and 48 hpi, which were validated by quantitative reverse transcription–PCR. Our results indicated that the resistance phenotype of GD66 was the consequence of recruiting a series of resistance genes involved in different regulatory pathways. WE-CLSM is a powerful technique for uncovering the mechanism of R. solani invading rice and for detecting rice sheath blight–resistant germplasm.